„Co z těch dětí vyroste?“ O rizicích oprese sociální práce vůči stejnopohlavním rodičům - Radka Janebová; Tereza Břízová; Ivana Velčovská (Gender a Výzkum)
Social work as an institutionalized profession aims to promote and defend human rights and social justice regardless of gender, sexual orientation and other grounds. Rooted in Christianity, it is partly performed by religious organizations and religious people. Consequently, conservative values may ​​orient the profession, thus conflicting with the rights of lesbians and gays. The aim of the article is to present the risks of social worker´s oppressive action toward same-sex parents, and to suggest possibilities how to avoid such ethical misconduct. First, we present a dilemma of social work arising from the tension between ethical principles of equality and non-discrimination on the one hand and conservative norms on the other hand. Then, we introduce individual oppressive tendencies which are manifested in the discourse “on homosexuality” in Czech social work and how these may transform into social worker´s oppressive action. Finally, we propose practical suggestions that can support anti-oppressive social work in the Czech Republic.